The interplay between Helicobacter pylori and the gut microbiota: An emerging driver influencing the immune system homeostasis and gastric carcinogenesis - Fakharian, Farzaneh; Asgari, Behnoush; Nabavi-Rad, Ali; Sadeghi, Amir; Soleimani, Neda; Yadegar, Abbas; Zali, Mohammad Reza (Frontiers in Cellular and Infection Microbiology, 2022)
The human gut microbiota are critical for preserving the health status because they are required for digestion and nutrient acquisition, the development of the immune system, and energy metabolism. The gut microbial composition is greatly influenced by the colonization of the recalcitrant pathogen Helicobacter pylori (H. pylori) and the conventional antibiotic regimens that follow. H. pylori is considered to be the main microorganism in gastric carcinogenesis, and it appears to be required for the early stages of the process. However, a non-H. pylori microbiota profile is also suggested, primarily in the later stages of tumorigenesis. On the other hand, specific groups of gut microbes may produce beneficial byproducts such as short-chain fatty acids (acetate, butyrate and propionate) that can modulate inflammation and tumorigenesis pathways. In this review, we aim to present how H. pylori influences the population of the gut microbiota to modify the host immunity and trigger the development of gastric carcinogenesis. We will also highlight the effect of the gut microbiota on immunotherapeutic approaches such as immune checkpoint blockade in cancer treatment to present a perspective for further development of innovative therapeutic paradigms to prevent the progression of H. pylori-induced stomach cancer.